Women’s changing opportunities and aspirations amid male outmigration: Insights from Makueni County, Kenya - Crossland, M.; Valencia, A.M.P.; Pagella, Tim; Mausch, K.; Harris, D.J.; Dilley, L.; Winowiecki, Leigh Ann (World Agroforestry Centre, 2021)
This brief presents a study on the changing opportunity spaces of men and women in the drylands of eastern Kenya (Crossland et al., 2021). It sheds light on the dynamics of rural aspirations in relation to both gender and age within the themes of outmigration and feminisation of agriculture. Using a novel methodology combining short narratives with semi-structured interviews and focus group discussions, this research contributes to a more nuanced understanding of aspirations and the wider socio-cultural context within which they are embedded and makes several recommendations for progressing aspirations research. The purpose of the research is to provide a better understanding of people’s current situations, desired trajectories and the influences that shape these aspirations, so that researchers and development actors might better tailor their support options to meet the needs of different user groups by matching technologies to their strategies and demands.